Piloting a dispersed and inter-professional Lesson Study using technology to link team members at a distance. Issue 5 (20th October 2017) - Koutsouris, George; Norwich, Brahm; Fujita, Taro; Ralph, Thomas; Adlam, Anna; Milton, Fraser
Abstract: This article presents an evaluation of distance technology used in a novel Lesson Study (LS) approach involving a dispersed LS team for inter-professional purposes. A typical LS model with only school teachers as team members was modified by including university-based lecturers with the school-based teachers, using video-conferencing and online video sharing. The aim was to examine the experiences of using video-conferencing and video transfer technology to support the use of LS procedures to connect team members between schools and university. The meetings from two LS teams (primary and secondary) were recorded and analysed using a discourse analysis framework, and team members were interviewed after the LS cycle. Despite some technical difficulties, the communication between the dispersed members of the teams was largely smooth and successful. Extending LS teams and practice to include non school teachers, using distance-linking technology, can more effectively support teachers, while reducing the practical constraints of bringing other professionals into the LS team.